Ecosystem tipping points due to variable water availability and cascading effects on food security in Sub-Saharan Africa - Celestine Muli; Nicolas Gerber; Tekalign Gutu Sakketa; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2018)
The frequency, duration, and magnitude of extreme weather events such as droughts, floods, and variation in rainfall onset and cessation periods will continue to increase. Such stress may result in significant shifts in the functioning of ecosystems. As climate change affects the capacity of ecosystems to mitigate the effects of extreme events such as drought and floods, leading to disruptions in water supply and food production, or to the destruction of infrastructure, human well-being is ultimately impacted. Chief among those impacts are those on the four dimensions of food security: food availability, accessibility, utilization, and stability. An interesting channel of impacts is through the observed and forecasted increase in the variability of water availability. This is said to cause uncertainty in agricultural production resulting in reduced productivity, food insecurity, weak economic growth and the widespread food poverty in Africa today. Due to overreliance on rain-fed agriculture in Sub Saharan Africa, people usually engage in both temporary and permanent migration after consecutive years of bad harvests and reduced incomes from agriculture with migration acting as an adaptation strategy to climatic shocks. Food value chains can be significantly affected, something that the paper identifies as an area that requires further research mainly on the resilience of food value chains to water variability.
Keywords: Q10; Q54; J43; J62; 330; Ecosystem; climate change; water variability; migration; food security; food value chains; Sub Saharan Africa